Pengaruh Sport Event dan Ketersediaan Fasilitas Halal Terhadap Minat Berkunjung Kembali Wisatawan Muslim ke Kek Mandalika dengan Destination Image Sebagai Variabel Intervening - Praditia, R Janitra Hendra; Saufi, Akhmad; Athar, Handry Sudiartha (Yayasan Pendidikan Intan Cendekia, 2022)
Tourist interest coming to Lombok is at a level that has not been maximized, this can be seen from the room occupancy rate which is not up to 50%. The purpose of this study was to determine the effect of sport events and the availability of halal facilities on the interest of returning Muslim tourists to Kek Mandalika with destination image as an intervening variable. The sample in this study amounted to 50 samples. The instrument used in this research is a questionnaire. Data were analyzed using multiple regression with the help of Partial Least Square (PLS) program. Based on the results of the study, it can be concluded that the influence of the Sport Event variable on the variable of interest in visiting again has a positive and significant effect. The effect of the variable Availability of Halal Facilities on the variable of interest in revisiting does not have a significant effect. The effect of the Sport Event variable on the Destination Image variable has a positive and significant effect. The effect of the Availability of Halal Facilities on the Destination Image variable has a positive and insignificant effect. The effect of the Destination Image variable on the variable of revisit interest has a positive and significant effect. The effect of Detination Image as a mediating variable or intervening Sport Event on the Interest to Visit Again. The mediation variable Destination Image does not mediate the variable Availability of Halal Facilities on Interest in Returning or is categorized as No Mediation